2017
DOI: 10.1097/md.0000000000007282
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone and renin in cardiac patients referred for catheterization

Abstract: Little is known regarding alterations of the renin-angiotensin system in patients referred for cardiac catheterization. Here, we measured plasma levels of active renin and aldosterone in patients referred for cardiac catheterization in order to determine the prevalence of elevated renin, aldosterone, and the aldosterone-renin ratio.A chemiluminescence assay was used to measure plasma aldosterone concentration (PAC) and active renin levels in 833 consecutive patients, after an overnight fasting and without any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Similarly, in the presented study, the RAS markers, in particular, the concentration of aldosterone and PRA in all patients of the study group was within the range of reference values. Our results are in a part consistent with the data of Erne et al 2017, which showed that in patients with AF associated with hypertension, an increased concentration of plasma renin was detected 2 times more often than in patients with AF without concomitant hypertension (35.3% vs 16, 5%, P = .005). The aldosterone concentration between patients of these groups did not differ …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, in the presented study, the RAS markers, in particular, the concentration of aldosterone and PRA in all patients of the study group was within the range of reference values. Our results are in a part consistent with the data of Erne et al 2017, which showed that in patients with AF associated with hypertension, an increased concentration of plasma renin was detected 2 times more often than in patients with AF without concomitant hypertension (35.3% vs 16, 5%, P = .005). The aldosterone concentration between patients of these groups did not differ …”
Section: Discussionsupporting
confidence: 93%
“…The aldosterone concentration between patients of these groups did not differ. 27 Thus, the levels of inflammatory markers defined in a whole group of patients with IsAF showed a general inflammatory response to the stress associated with cardiac arrhythmia. Analogous results were previously demonstrated by other researchers.…”
Section: Discussionmentioning
confidence: 93%
“…The first one, extracellular superoxide dismutase (Cu-Zn SOD), is a major antioxidant enzyme whose alterations possibly reflect enhanced oxidative stress; moreover, impaired Cu-Zn SOD expression or catalytic activity has been identified in several physiological situations such as aging and age-associated diseases (30). The second one is renin, which was the strongest correlate of CAD in our cohort and whose link with cardiovascular events has a firm pathological basis and is supported by growing clinical evidence: renin is the activator of the renin-angiotensinaldosterone system, whose pharmacological inhibition reduces morbidity and mortality of patients with CAD (31), and high levels of renin are associated with atherosclerosis, hypertensive cardiomyopathy, and impaired left ventricular function (32). The observational Multiethnic Study of Atherosclerosis reported an independent association between plasma renin activity and cardiovascular outcomes in patients without previous CV events who had angiographically proven CAD or subclinical cardiovascular disease (33).…”
Section: Discussionsupporting
confidence: 59%
“…One notable strength of our study is that we specifically focused on patients with “apparently” idiopathic AF who were still at the early stage of AF and ruled out patients using antihypertensive medications. A common methodological flaw observed in previous studies investigating the relationship between the RAAS and AF is the failure to account for the influence of antihypertensive drugs in their regression models [30] .…”
Section: Discussionmentioning
confidence: 99%